THE EFFECT OF JOB SATISFACTION ON ORGANIZATIONAL COMMITMENT-AN ANALYTICAL STUDY - THE MUNICIPALITY OF BAGHDAD AS A MODEL - Wafaa Salem Abd Alhassan; Husam Jasim Mohammed (Scholar Express Journals, 2025)
This study seeks to examine the effect of the correlation between job satisfaction and organisational commitment among employees in the Municipality of Baghdad, specifically within the Second Sadr Municipality Department. The study investigates the influence of job satisfaction, determined by elements such as working conditions, remuneration, interpersonal interactions with colleagues and management, and prospects for professional progress, on the enhancement of organisational commitment among municipal employees. The study employed a quantitative methodology utilising questionnaires administered to a random sample of employees from the Second Sadr Municipality. The data were examined with statistical techniques to determine the correlation between work satisfaction and organisational commitment. The research findings indicate a robust correlation between job satisfaction and organisational commitment in the second municipality of Sadr, revealing that employees who experience heightened satisfaction with their work environment and job conditions exhibit increased commitment to the institution. Job satisfaction substantially influences emotional commitment, as employees have a sense of connection and loyalty to the organisation when they are content with their work conditions. Content to remain in the profession due to the advantages and remuneration they obtain. Research has demonstrated a strong correlation between job happiness and organisational commitment; thus, enhancing job satisfaction may be pivotal for augmenting organisational commitment and attaining institutional success in the Second Sadr Municipality. The primary recommendations of this research are to augment job satisfaction among employees of the Second Sadr Municipality by enhancing the work environment, offering suitable incentives, focussing on employee skill development, and fostering improved relations between staff and management. This fosters heightened organisational commitment and bolsters employment stability within the municipality
Keywords: Job Satisfaction; Organizational Commitment; Analytical Study